(untitled) (PHRASIS | Rivista di studi fraseologici e paremiologici, 2021)
This article takes up the theme of the importance of a diachronic vision of regional phraseology in the study of Cuban Spanish and based on a new analysis, where the synchronic with the diachronic is combined, its author argues and exemplifies the essential aspects that they have to do with the variation of those UFS that were taken from the Hispanic oral tradition by Spanish writers during the sixteenth and seventeenth centuries and that, thanks to the dynamics of conservation and constant renewal, have taken root in the Cuban variant of Spanish. With this work, based on the contrastive analysis of literary sources with the current use of phraseological units in a region of Cuba, a line of research on the historical phraseology of this country is continued and new work perspectives are opened.